2020
DOI: 10.22207/jpam.14.spl1.46
|View full text |Cite
|
Sign up to set email alerts
|

South Korea’s COVID-19 Infection Status: From the Perspective of Reconfirmation after Complete Recovery

Abstract: COVID-19 started to occur in South Korea by an inflow of the virus from abroad, when a traveller from Wuhan, China, was first confirmed on January 19th, 2020. Although South Korea reduced the number of newly confirmed cases and is on the way to stabilizing the situation with its disease prevention policies, problems remain. The main issue is the reconfirmation of the virus after recovery. South Korean experts believe the reconfirmed cases are caused by reactivation of the virus inside the patients’ body, rathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 3 publications
0
11
0
1
Order By: Relevance
“…Serum antibodies were not detected at the beginning of the second symptomatic period, which can represent an incomplete immune response that left the infection temporarily dormant, only to be re-activated again; and even though the patient was symptomatic and had had occupational contact with infected patients during her symptom-free recovery period, re-activation was considered more probable than re-infection (32). Similar studies have reported a return of mild or even severe symptoms; but within a short time frame and without genetic analysis of the infective pathogens, they were reported to be cases of reactivation rather than re-infection (33)(34)(35)(36).…”
Section: The Rst Follow-up Rt-pcrmentioning
confidence: 95%
“…Serum antibodies were not detected at the beginning of the second symptomatic period, which can represent an incomplete immune response that left the infection temporarily dormant, only to be re-activated again; and even though the patient was symptomatic and had had occupational contact with infected patients during her symptom-free recovery period, re-activation was considered more probable than re-infection (32). Similar studies have reported a return of mild or even severe symptoms; but within a short time frame and without genetic analysis of the infective pathogens, they were reported to be cases of reactivation rather than re-infection (33)(34)(35)(36).…”
Section: The Rst Follow-up Rt-pcrmentioning
confidence: 95%
“…They had positive test results after 18 and 21 days of two consecutive negative results for nasopharyngeal swabs [ 19 ]. On 17 April 2020, a case report from South Korea highlighted that 163 out of 7829 patients (2.1%) were tested positive and most of them (66.9%) were women [ 20 ]. Another case report from Italy identified a 48-year-old man who had a severe form of COVID-19.…”
Section: Reports On Re-positive Pcr Assay After Dischargementioning
confidence: 99%
“…Re-infection unlikely 15 Kang et al. [ 20 ] South Korea, Apr 2020 163 53 (33.1%) (20–29) most of them Nasopharyngeal 13.5 (1–35) 61 Mild symptoms Reactivation 16 Loconsole et al. [ 21 ] Italy, May 2020 1 1 (100%) 48 Nasopharyngeal 30 1 Moderate symptoms Reactivation 17 Dou et al.…”
Section: Reports On Re-positive Pcr Assay After Dischargementioning
confidence: 99%
See 1 more Smart Citation
“…Assuming that the immune response is incomplete following a normal viral infection and re-infection is possible, reinfection can be defined as clinical recurrence of COVID-19-compatible symptoms with a positive PCR test. Although many studies have been conducted in China [3][4][5] Korea [6] USA [7] Brazil [8] about this matter, however, the available evidences are not enough and further studies can provide more accurate statistics about reinfection.…”
Section: Introductionmentioning
confidence: 99%